2021
DOI: 10.17969/jimfp.v6i4.18331
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Konsentrasi Pupuk Organik Cair terhadap Pertumbuhan dan Hasil Beberapa Varietas Tanaman Tomat (Lycopersicum esculentum Mill.)

Abstract: Abstrak. Penelitian ini bertujuan untuk mengetahui pengaruh konsentrasi pupuk organik cair dan varietas yang tepat serta interaksi antara kedua faktor tersebut terhadap pertumbuhan dan hasil tanaman tomat. Penelitian ini dilaksanakan di Desa Peparik, Kecamatan Blangjerango, Kabupaten Gayo Lues dan Laboratorium Dasar Kampus USK PSDKU Gayo Lues, berlangsung dari bulan Januari sampai Maret 2021. Rancangan Penelitian yang digunakan adalah Rancangan Acak Kelompok pola faktorial 4x3 dengan 3 ulangan sehingga terdapa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
0
2
0
2
Order By: Relevance
“…If the dose given is excessive or low, it will cause the photosynthesis process not to be optimal, and photosynthesis will decrease. Agustina (2015) stated that if too much nutrition is given to plants, plant growth will be disrupted, or the plant will be poisoned. If the dose given is low, it will not affect the plant.…”
Section: Number Of Leavesmentioning
confidence: 99%
See 1 more Smart Citation
“…If the dose given is excessive or low, it will cause the photosynthesis process not to be optimal, and photosynthesis will decrease. Agustina (2015) stated that if too much nutrition is given to plants, plant growth will be disrupted, or the plant will be poisoned. If the dose given is low, it will not affect the plant.…”
Section: Number Of Leavesmentioning
confidence: 99%
“…Furthermore, the results of research by Wijiyanti et al (2019) showed that the application of rice-washing water fertilizer without incubation had a significant effect on the number of leaves, leaf area, wet weight and dry weight of green mustard greens. Agustina et al, (2015) stated that the elements nitrogen, phosphorus, and potassium are very important for plants, including parts related to generative development which causes metabolism in the plant body to be better. This can be seen from the research results through the correct application of Organic NPK, which has increased plant growth.…”
Section: Dry Weightmentioning
confidence: 99%
“…Pupuk organik cair memberikan pengaruh nyata terhadap pertumbuhan dan hasil tanaman tomat pada berbagai varietas (Yanti et al, 2021). Pupuk organik memiliki unsur hara makro dan mikro yang dapat menggantikan penggunaan pupuk AB-Mix yang umum digunakan dalam proses budidaya hidroponik.…”
Section: Pendahuluanunclassified
“…Prosedur penggunaan bokhasi pada tanaman adalaht: 1) pupuk bokashi dicampur dengan tanah untuk media tanam dengan perbandingan 1:1, dan pupuk di berikan secukupnya sesuai dengan kebutuhan pada media tanam pada bedengan. 2) Pupuk Bokashi ditaburkan di sekeliling tanaman.. Banyak hasil penelitian yang melaporkan pengaruh positif terhadap penggunaan bokashi, dengan kisaran dosis pemakaian 15 -20 ton/ha pada tanaman mentimun, tomat, dan kangkung (Rusnani et al, 2021;Wiratama dan Syakur, 2021;dan Zulman et al, 2022).…”
Section: Peningkatan Pemahaman Masyarakatunclassified